The position of abusive clauses in Iranian Law - Yamrali, Saleh (Opción, 2019)
The contract terms that one party imposes by exploiting its economic, social and specialty status on the weaker party and the consumer, which has not been negotiated independently, are considered as abusive clauses. These terms are fundamentally void and ineffective. In Iran's law, annulment of these terms depends on the "Principle of No-Harm" and "Abuse of Rights Principle", which is explicitly emphasized in article 40 of the constitution of Iran. The unequal terms contained in the "automobile supplier-consumer contracts", "heavy liquidate damages between banks and customers" and "terms in electronic contracts" are among the instances.